1977
DOI: 10.2190/9wa2-rvl3-mt9d-el9d
|View full text |Cite
|
Sign up to set email alerts
|

Prosperity as a Cause of Death

Abstract: The general death rate rises during business booms and falls during depressions. The causes of death involved in this variation range from infectious diseases through accidents to heart disease, cancer, and cirrhosis of the liver, and include the great majority of all causes of death. Less than 2 percent of the death rate-that for suicide and homicide-varies directly with unemployment. In the older historical data, deterioration of housing and rise of alcohol consumption on the boom may account for part of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
7

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(61 citation statements)
references
References 43 publications
3
50
1
7
Order By: Relevance
“…The fact that population health tends to evolve better in recessions than in expansions was first noted decades ago (18)(19)(20), but was largely ignored until recently, when several studies reported this relationship using data from the latter half of the twentieth century (14)(15)(16)(21)(22)(23)(24)(25)(26). A number of mechanisms may explain the effects of business cycles on health (11, 15, 19-21, 23, 24, 27-30).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that population health tends to evolve better in recessions than in expansions was first noted decades ago (18)(19)(20), but was largely ignored until recently, when several studies reported this relationship using data from the latter half of the twentieth century (14)(15)(16)(21)(22)(23)(24)(25)(26). A number of mechanisms may explain the effects of business cycles on health (11, 15, 19-21, 23, 24, 27-30).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include air pollution and traffic congestion, which rise with economic activity and may have particularly strong effects on the mortality of vulnerable segments of the population (Braga, Zanobetti, and Schwartz 2001;Brunekreef and Holgate 2002;Clancy et al 2002;Peters et al 2004). Geographic migration, induced by economic expansions, could similarly increase social isolation and reduce community support, with particularly detrimental impacts for the old and young (Eyer 1977;Tapia Granados 2005b). Heightened intensity of employment may also make it harder for workers to care for their aged dependents (Vistnes and Hamilton 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of the relationship between macroeconomic conditions and CVD mortality primarily used economic indicators such as per capita gross domestic product (GDP) or unemployment as proxies for economic conditions or instability and examined data using time series analyses (18,19,46,51,159). Some studies indicated a potential positive relationship between economic conditions and heart disease mortality, but in many cases, these were highly sensitive to model specifications and hypothesized lag times.…”
Section: Macroeconomic Factors and Cvdmentioning
confidence: 99%